Sweet Charity - Simon, Neil 1927-2018; Fellini, Federico 1920-1993; Pinelli, Tullio 1908-2009; Flaiano, Ennio 1910-1972; Surtees, Robert 1906-1985; Coleman, Cy 1929-2004 (Universal studios, 2020)
"The feature debut of the great Bob Fosse based on the Broadway hit, Sweet Charity is a musical re-imagining of Federico Fellini’s Nights of Cabiria, starring the wonderful Shirley MacLaine as a taxi dancer looking for love and escape in hippy-era New York." [powerhousefilms.uk]
Original: USA 1969
Limited edition Blu-Ray special features: 4K restoration ; three presentations of the film: with original overture (150 mins); without overture (149 mins); and with alternative ending (145 mins) ; alternative 2.0 stereo and 5.1 surround soundtrack options ; audio commentary with film historians Lee Gambin, Alexandra Heller-Nicholas and Cara Mitchell (2020) ; "The John Player Lecture with Shirley MacLaine" (1971, 81 mins): archival audio recording of the celebrated actor in conversation at London’s National Film Theatre ; "From stage to screen: a director’s dilemma" (1969, 9 mins): original promotional film featuring interview material with Bob Fosse and rare behind-the-scenes footage ; "The art of exaggeration" (1969, 8 mins): original promotional film profiling the work of famed costume designer Edith Head ; "Interview with Sonja Haney" (2020, 70 mins): audio recording of the dance assistant in conversation with Lee Gambin ; "Now and then: Sammy Davis Jr" (1968, 23 mins): archival interview featuring the actor and singer in conversation with broadcaster Bernard Braden ; Super 8 version: original cut-down home-cinema presentation ; image gallery: publicity and promotional material ; original theatrical trailer ; new and improved english subtitles for the deaf and hard-of-hearing ; limited edition exclusive 80-page book with new essays by Pamela Hutchinson and Bill Rosenfield, Neil Simon on "Sweet Charity", archival press coverage of the film’s release including an interview with Shirley MacLaine, extracts from the pressbook, Federico Fellini on "Sweet Charity", an overview of contemporary critical responses, and film credits ; limited edition exclusive double-sided poster ; UK premiere on Blu-ray ; limited edition of 3,000 copies
Bildformat 2.35:1
Keywords: Film; Blu-Ray-Disc